Water Sustainability: Current and Future Challenges at SRM Institute of Science and Technology, Chennai, India - Pachamuthu, Sathyanarayanan; Sancheti, Sandeep; Sethuraman, N.; Thirumurugan, V. (Journal of Sustainability Perspectives, 2021)
SRMIST has healthy approach to sustainability, incorporating social economic and environmental principles that have been in place for nearly a decade implementing short and long-term sustainable objectives. SRMIST developed, maintained the estate, and the surrounding landscape, with due environmental impact and social values and implemented effective, efficient utility management measures, policies and procedures. The 2018/2019 UI Green Metric ranked SRMIST as 9 th in India and 392nd in Global Ranking overall and 264th rank globally and 9th rank in India for water parameter and 3rd in the Nation and 243rd globally and 2nd rank nationally and 42nd rank globally for water. SRM IST improved implementation of the water conservation and recycling program from 75% in 2018 to 95 % in 2019. Water efficient appliances increased > 70% and has a long-term commitment for conservation of water by regularly monitoring the use of water with regular meters. SRMIST has 20 RO plants running 24x7 collecting 31,000L per day for all and installing Ultra Filtration unit. SRMIST’s goal is to reduce per capita water consumption varies from 3.7m3 to 3.3m. Among the 4600 M3 waste water generated an average 4140 M3 wastewater is treated and recycled. Rainwater harvesting pits have been constructed in 65% college buildings and hostels is used for the water recharge in the campus and the rainwater stored in the roof tanks are used for toilet flushing.